An Analysis of the PAI Curriculum in Enhancing Interreligious Tolerance at a Muhammadiyah Islamic Vocational High School - Winoto Pamungkas, Adityo Harjo; Nurazizah, Eva; Belawati Pandiangan, Anjani Putri; Cahlia, Silva (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2025)
Abstract: This study aimed to examine the planning, implementation, and evaluation of the Islamic Religious Education (PAI) curriculum implemented at the Muhammadiyah Technical School within a multicultural learning context. It also investigated the contribution of the PAI curriculum implementation to the development and enhancement of interreligious tolerance among members of the school community. The study employed a descriptive qualitative approach. Data were collected through participatory observation, structured interviews, and document analysis involving PAI teachers, vice principals for curriculum affairs, and students at the Muhammadiyah Technical School. The findings indicated that the Muhammadiyah Technical School successfully integrated Islamic values into the curriculum without neglecting the principles of religious tolerance, by fostering an inclusive learning environment that encouraged respect for differences and interreligious collaboration.